No evidence of mycobacterium tuberculosis in dogs living with pulmonary tuberculosis patients - Fernández C., Carla (2012)
Tuberculosis (TB) is an infectious disease primarily of humans which produces high morbidity and mortality. Dogs are also susceptible to Mycobacterium tuberculosis infections; therefore, the present study searched for evidence of the presence of this pathogen in 58 dogs that live with human pulmonary TB patients in Lima, Peru. Chest Xray was performed and pharyngeal swab, saliva, bronchial fluid, urine and feces samples were taken from dogs. Fluorescence microscopy was performed with auramine O staining and TB culture by the Löwenstein Jensen and the Microscopic Observation Drug Susceptibility (MODS) methods. Epidemiological data was collected to define the patient-pet relationship. The custom of spitting on the floor of the house, the dog licking patient’s sputum and the affective contact with the pet were practices identified during the study that might facilitate the transmission of M. tuberculosis from human to pets. However, none of the dogs presented clinical or microbiological evidence of TB. Transmission of MTB in dogs that live with pulmonary TB patients could not be determined.